Pengaruh Lokasi, Harga, dan Atribut Toko Terhadap Keputusan Pembelian Pada Toko Malika Papar di Kediri - Novita Mayang Sari; Baju Pratmutoko; Nurali Agus Najibul Z. (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to determine the effect of location, price, and store attributes on purchasing decisions at Toko Malika. The location of this research was conducted at the Toko Malika, Jl. Raya Papar-Pare No. 03 Papar Village, Papar District, Kediri Regency, East Java 64153. The object of this research is the consumers of Malika Papar Shop, Kediri. This research is a quantitative research. Data collection was carried out using interviews, observation, documentation, and questionnaires. Data analysis was carried out using the validity test, reliability test, correlation test, multiple linear regression test, T test, F test and the coefficient of determination (R2). The results of the research that has been done indicate that there is a strong relationship between location, price, and store attributes variables on purchasing decisions to buy at Malika Papar Kediri store. This is evidenced by the multiple R value of 0.696, the correlation coefficient (relationship) can be said to be very strong with consumer perceptions in deciding to buy at malika's shop, Papar Kediri.